Biodiversity of Soil Microbes from Rhizosphere at Wamena Biological Garden (WBiG), Jayawijaya, Papua - SRI WIDAWATI; SULIASIH SULIASIH; H. J.D LATUPAPUA; ARWAN SUGIHARTO (Biodiversitas Journal of Biological Diversity, 2005)
The isolation, identification and population of soil microbes from rizosphere at WBiG had been done in the Soil Laboratories Microbiology, Microbiology Division, Research Center of Biology, Indonesian Institute of Sciences (LIPI), Bogor. The soil was collected randomly from 16 sites in WBiG, and taken from 0-15 cm depth. Isolates of microbes were identified by Bergeys manual method for bacteria; Ellis method for fungi, and the morphology of isolate method for Actinomycetes. The population of microbes was estimated by plate count method. The result of isolation, identification and population soil microbes from 16 samples in WBiG showed that 20 isolates of bacteria (Azotobactersp., Accinetobacter sp. , Bacillus sp., Citrobacter sp., Flavobacterium sp., Klebsiella sp., Nitrosomonas sp., Pseudomonas sp., Rhizobium sp., Thiobacillus sp., Azospirillum sp., Azotobacter chrococcum, Bacillus panthothenticus, Chromobacterium violaceum, C.lividum,Escherrrichia coli, Flavobacterium breve, Klebsiella aerogenes, Spaerotillus natans, and Staphylococcus epidermidis); nine isolates of fungi (Aspergillus niger, Bisporomyces, Monilia sp., Cephalospharium sp., Verticillum sp., Giocladium sp., Penicillium sp., Nelicocephalum sp., and Cuninghamella sp.), and seven isolates of Actinomycetes (Streptomyces, Streptosporangium, Nocardia, Thermomonospora,Thermoactinomyces, Micromonospora, Mycobacterium). The population of Bacillus (108-109), Rhizobium (106-107), Azospirillum (106-107),and Thiobacillus (104 -109 ) were founded all of soil samples.ïƒ“ 2005 Jurusan Biologi FMIPA UNS SurakartaKey words: soil microbes, Wamena Biological Garden (WbiG).